"Balancing the Partner's Contribution" - Analyzing the Risks and Benifits in the case of an Indian Joint Venture. - gautam, mukim (2006)
Joint Venture is used as it has the tendency to evolve where there is a need to implant hierarchy to enable future strategic decision-making in cases where single firm alternatives are inferior or prohibited. (Kay,N.M. 1997) A Joint Venture can be defined an agreement between two or more firms, leading to the establishment of a separate legal entity. The firms may be held responsible for their own individual tasks for which they have special expertise, knowledge or past achievements. For instance, a new firm might be responsible for supplying inputs for a subset of the firms, conducting research and development activities or downstream activities such as marketing and distribution of the products. The participants in a Joint Venture agree to share capital, human resources, risks, profits, technology that may be needed for the formation of the separate entity under shared control. Fuji-Xerox is an example of a successful joint venture. The Post World War II diversification strategies of large corporations and the existence of globalization have led to a rapid proliferation of strategic alliances. The presence of an increasing number of alliances between firms is especially felt in the case of developing countries. Countries like India and China now provide the best examples for alliance strategies that result in a Joint Venture, or in Business Process Outsourcing, Mergers etc. as these countries stand on the cusp of explosive growth.